The Influence of The Oketani Massage Method on Lactation among Postpartum Women - Rahayu, Duwi Puji; Martiningsih, Wiwin; Abiddin, Andi; Damo, John Leones (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Breast milk is the most important nutrient for fulfilling the growth and development needs in infants. Obstacles during exclusive breastfeeding to infants are usually caused by non-breast milk and a lack of production of breast milk, which is usually due to insufficient stimulation of the prolactin and oxytocin hormones. The objective of this study was to determine breast milk production in postpartum mothers. Experimental research design using pre-experimental design in the form of the one-shot case study. The sampling technique used was consecutive sampling, obtained a many as 26 respondents. This research was conducted in February-March 2024 at Dr. Soedono Madiun Hospital. The results found that breast milk production in mothers increased after Oketani massage. The breast milk will be 100% out when massage is done on day 1 afternoon and maximum on day 3 morning, when massage is done 2x a day. So this study states that this massage is very effective in increasing breast milk production. After this study, respondents already knew how to do breast care in the form of Oketani massage. And so that they can do this massage regularly at home, so that it can facilitate and increase breast milk production.